Structures/textures of living/fossil microbialites and their implications in biogenicity: An astrobiological point of view - Rizzo, Vincenzo (2015)
Atacama’s microbialites, able to live in such extreme environment, are possible candidates as models for searching life in other planets or moons. At present, little is known about their microstructure and composition. This study analyzes, mainly, the terrestrial microstructures in a dimensional field longer than 0.1 mm, through an original approach using photographs and macro pictures, appropriately magnified and consequently little defocused, in comparison with analogous images shot by NASA Rovers on Martian outcroppings. A method able to permit comparison of structures and textures of terrestrial microbialites to the microscopic photo images (MI) shot by the cameras mounted on the NASA rovers that since more ten years are present on the Red Planet (Opportunity, Spirit, Curiosity). The study highlights occurrence of widespread structures likes microspherules (or clots), often organized into some higher order settings, such are donuts, polispherules, filaments and, above all, intertwined filaments of microspherules, all showing features of an imperfect geometrical repetitiveness. The structural analysis has been connected with a textural study by a multifractal analysis, that is able to distinguish terrestrial biogenic stromatolites from abiogenic pseudo-stromatolites, and giving us a tool that might be applied for astrobiological purposes.